Efektifitas Media Pembelajaran Video Scribe Dalam Bahasa Inggris Pada Simple Present Tense - Supiningsih Supiningsih (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2019)
This study aims to improve learning achievement in English by applying scribe video learning media. The research subjects of class X TKR 2 were 32. The object of the research was the process of learning English in the present tense material with the application of scribe video learning media. The method of this research is Classroom Action Research using two cycles in a continuous manner. The technique of collecting data uses observation, documentation and tests. The results of the study are the application of scribe video media can improve students' learning achievement in class X TKR 2, indicated by an increase in the average grade value from the initial condition 74.70 to 78.1 and an increase in mastery learning from the initial condition 20 increased to 27.